Time-resolved photoluminescence studies of stimulated emission and exciton dynamics in ZnSe/ZnS0.18Se0.82 superlattices - Stevens, C; Taylor, R; Ryan, J; Dabbicco, M; Ferrara, M; Cingolani, R; Kuroda, Y; Suemune, I (1994)
We report measurement of time resolved photoluminescence from ZnSe/ZnSSe superlattices. We observe an anomalous fast-decay component in the luminescence at an energy corresponding to that at which stimulated emission is observed at higher pump densities. From consideration of the risetimes and spectral position of the lasing line, we infer an excitonic scattering mechanism to be responsible for lasing in these samples. © 1994.